Metode Altman Z-Skor Dalam Memprediksi Kepailitan Di Semua Koperasi Kredit Di Kabupaten Maumere - Yoseph Darius Purnama Rangga; Henrikus Herdi; Wilhelmina Mitan (ITB AAS INDONESIA, 2020)
Abstract Problems that often occur in a cooperative are usually caused by financial problems. To measure the level of financial health cooperatives can be used analysis of financial ratios using the Altman Z-Score model. This research aims to predict bankruptcy in the credit Union of the regional government Puskopdit, Maumere, using the Altman Z-Score model. The samples in this study were credit cooperatives of the main district Puskopdit in 2015-2017 consisting of 16 cooperatives. The data source used is the secondary data in the form of cooperative financial statements. The analytical technique used is the Altman Z-Score Bankruptcy Prediction model. The results showed that there is a cooperative that has been in the healthy category during the year 2015-2017, namely Torch Mas Cooperative, Tuke Jung, Ortal, Plantation, star East, and Serba Te. In the years 2015 and 2016 Kelubagolit cooperatives entered in the category of gray area, but in the year 2017 the cooperative is in a healthy category. In addition, there are cooperatives during the year 2015-2017 in the category of gray area namely Sube Huter Cooperative, Tuke Ler, Hiro Heling, Bina Pertiwi, and Surya Sakti. The cooperatives of San Dominggo in 2015 and 2016 were in the category of bankruptcy, but the following year entered the gray area category. The cooperative in the category of bankruptcy from 2015-2017 is the youth cooperative Hokeng and Ankara. In the year 2015 Plelu Meluk Cooperative entered in the category of gray area, the cooperative's performance continued to decline and in the year 2016 and 2017 the cooperative was entered in the category of bankruptcy. In the years 2018, Hokeng Youth Cooperative experienced an amalgamation with Mitan Gitan Cooperative. This indicates that the accuracy level of the Altman Z-Score model is high..